INTEGRASI STEAM-PjBL PADA PEMBELAJARAN IPA DI SMP NEGERI 3 KARANGMOJO, BANTUL–YOGYAKARTA: PROYEK MIKROSKOP SEDERHANA - Supriyatin, Supriyatin; Rahayu, Sri; Suhadi, Anggi Putri; Simarmata, Remli Nelmian (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. Many teachers still have not integrated STEAM-PjBL in learning. Students who are accustomed to conventional learning and have never operated a microscope as a tool in understanding science material. STEAM-PjBL learning is the right solution in facilitating and providing space for students to be able to overcome these problems, STEAM-PjBL is also a place to hone students' abilities and skills to face the demands of the current modernization era. The purpose of this activity is to introduce, implement and integrate STEAM-PjBL in science learning. The population in this activity is all 8th grade students of SMP 3 Karangmojo and the subject of the activity is class 8 B with a total of 30 people. The activity will be held on July 15, 2022. The stages of STEAM-PjBL integration consist of Reflection, Research, Discovery, Application and communication. The activities that have been carried out have given positive results, 80% of students